Pathophysiology and Management of Primary Osteoporosis: A Narrative Literature Review - Dendi Andrean; Najirman; Eka Kurniawan (HM Publisher, 2023)
The pathophysiology of primary osteoporosis primarily involves changes at the cellular and bone tissue levels. This process involves an imbalance between the activity of bone-destroying cells (osteoclasts) and bone-constructing cells (osteoblasts). Osteoclasts are responsible for the resorption of old and damaged bone tissue, while osteoblasts build new bone. In osteoporosis, osteoclast activity increases and osteoblasts decrease, resulting in loss of bone mass. Treatment of primary osteoporosis involves a holistic approach that includes lifestyle changes, use of medications, and fracture prevention. The main goal of management is to slow down the decline in bone density, prevent bone fractures, and improve the quality of life of sufferers. Increasing your intake of calcium and vitamin D, as well as regular physical exercise, can help maintain bone mass. Meanwhile, drugs such as bisphosphonates and teriparatide can be used to inhibit bone breakdown or stimulate new bone formation.